Post-mortem toxicological investigations in a paediatric population - Louw, Ané (Division of Forensic Medicine and Toxicology, 2020)
In South Africa, little is known about the presence of drugs in infant cases admitted for post-mortem medico-legal examinations,as toxicological investigations are not routinely performed. It was hypothesised that drugs would be detected in sudden and unexpected death ofinfant (SUDI) cases admitted to Salt River Mortuary (SRM), as infantsform a vulnerable population. Biological samples (blood, vitreous humour, urine and hair) were collected from 30 infants who were admitted as SUDIcasesto Salt River Mortuary,Cape Town,between 28 May 2019 and 17 October 2019. Samples were screened for at least 750 common drugs using a SCIEX X500R QTOF. Demographic variables, social circumstances and clinical historywere recorded from the medico-legal case folder. Of the 30 SUDI cases, drugs were detected in 25 (83 %) cases, with acetaminophen (61 %) and caffeine (54 %) being most prevalent. Methaqualone (32 %) and methamphetamine (11 %),two commonly abused drugs in the Western Cape,werealsoidentified, with the former only present in hair. There were significantly more drugs detected in hair samples compared to the other samples (p < 0.0001). Therefore, while challenging in its interpretation, hair analyses provideda wealth of information concerningpossiblelonger-termdrug exposure in infants.This was particularly valuable inrevealingmethaqualoneexposure, which may have otherwise gone undetected, and which may indicate an environment of neglect. While the cause of death in most cases was natural (infectious causes) (63 %), next-of-kin seldom declared that their infant exhibited symptoms of illness orthat medication was administeredprior to death. Therefore, theresults of this study illustrate the valueof toxicological testing in SUDIcases at SRM, as well as the need to analyse multiple samples. This study provides empirical data to motivate for the SUDI investigation protocolatSRM toinclude routine toxicological analysis. This is anticipated toadd value to the medico-legal investigation as well as add social value to the lives of siblings who may also be at risk for neglect.